Enhancing Microgrid Voltage and Frequency Stability through Multilayer Interactive Control Framework - Moussa Saadati Toularoud; Mohammad Khoshhal Rudposhti; Sajad Bagheri; Amir Hossein Salemi (International Transactions on Electrical Energy Systems)
Microgrids (MGs) play a crucial role in modern power distribution systems, particularly in ensuring reliable and efficient energy supply, integrating renewable energy sources, and enhancing grid resilience. Voltage and frequency stability are paramount for MG operation, necessitating advanced control frameworks to regulate key parameters effectively. This research introduces a multilayer interactive control framework tailored for MGs utilizing distributed energy resources (DERs). The framework comprises primary control layers, integrating internal voltage and current controller loops, and secondary layers employing distributed finite-time control (DFTC) strategies. Through simulation studies and comparative analyses with traditional proportional-integral (PI) controllers, the effectiveness of DFTC controllers in reducing initial oscillations and improving stability is demonstrated. Major findings include the superior performance of DFTC controllers in stabilizing voltage and frequency parameters, optimizing power output, and enhancing overall operational efficiency. Additionally, insights into the operational dynamics of MG systems highlight the significance of advanced control strategies in mitigating fluctuations and ensuring system stability. Furthermore, the proposed method demonstrates significant efficacy improvements over conventional approaches. Voltage stability is enhanced with oscillation amplitudes less than 0.01 pu, active power control achieves a stable level of 0.93 pu, and frequency fluctuations are reduced to 0.004 Hz and effectively recovered to 0.002 Hz. These improvements suggest that the proposed method enhances system stability and control precision by approximately 95% compared to conventional methods, as it achieves much tighter control over voltage, active power levels, and frequency fluctuations.